Inovasi Usaha Sambel Cumi Dengan Kemasan Standing Pouch Menggunakan Teknologi Streilisasi Komersil - Mila Fatmawati; Herman Darwis; Gunawan Gunawan; Nurjanna Albaar; Hamidin Rasulu (Jurnal Pertanian Khairun, 2026)
The increasing demand for ready-to-eat seafood products with extended shelf life has encouraged the development of innovative processing and packaging technologies that ensure food safety while maintaining product quality. Squid chili sauce is a promising value-added seafood product with high market potential; however, its high moisture and protein contents make it susceptible to microbial spoilage and quality deterioration during storage. This study aims to develop an innovative squid chili sauce packaged in a retortable standing pouch using commercial sterilization technology to improve product safety, shelf stability, and business competitiveness. The research employs a research and development (R&D) approach integrated with laboratory experiments. Fresh squid is processed into chili sauce, packaged in multilayer retort standing pouches under vacuum conditions, and subjected to commercial sterilization using a retort system at 121°C with different processing times. Product quality is evaluated through physicochemical, microbiological, and sensory analyses, while shelf-life performance is assessed during ambient storage. In addition, a business feasibility analysis is conducted by examining production costs, break-even point, revenue-cost ratio, and market potential. The application of commercial sterilization technology is expected to produce a shelf-stable squid chili sauce without the need for chemical preservatives while preserving desirable sensory characteristics and nutritional quality. Furthermore, the integration of retortable standing pouch packaging is anticipated to enhance product portability, distribution efficiency, and consumer acceptance. This innovation is expected to provide an effective technological solution for small and medium-sized seafood enterprises by increasing product value, expanding market opportunities, supporting sustainable seafood processing, and strengthening the competitiveness of Indonesian seafood products in domestic and international markets.